Making an Electric Vertical Jump Limb Muscle Explosiveness Test Tool Using Iot Technology in Physical Education Activities - Candra, Juli; Indrayana, Boy; Sagala, Ramlan Sahputera; Daulay, Dicky Edwar (Journal Coaching Education Sports, 2025)
This research aims to design and develop an Internet of Things (IoT) technology-based leg muscle explosiveness test tool that can be used in physical education activities. The research design is in the form of an electric vertical jump tool, students only need to stand and jump in front of the media that we have made so that the results can be converted automatically. The research method includes the design stage, tool development, and testing of 30 high school students. The test results show that this tool has high validity with a correlation (r = 0.93) to the manual method, and provides accurate and consistent data. In addition, the survey showed that 90% of users found the tool easy to use thanks to the app-based digital interface that allows real-time data analysis. This tool makes a significant contribution in improving the accuracy and efficiency of leg muscle explosive power measurement, and is relevant for use in modern physical education. However, limitations such as the need for internet connection and manufacturing costs need to be overcome to increase wider adoption. This study concludes that an IoT-based leg muscle explosive power testing device has great potential to improve the quality of physical evaluation in physical education and sports training environments.